MODERN IMMUNODIAGNOSIS OF DISEASES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
It is commonly believed that the function of the immune system is to protect the body from pathogens, foreign and safe mechanisms that have entered the human body from the outside. However, it also protects us from within, producing large-scale tumors and helping to destroy destructive cells [4,8,9].